Biochemistry - Voet, Donald (New York : Wiley, 1995)
Updated to reflect current biochemical practices, this text emphasizes the more extensive use of molecular techniques in human disease research. It includes extensive material on molecular biology, and presents biochemistry from a chemist's perspective.
Keywords: BIOCHEMISTRY